Montado intangible heritage in Southern Portugal - Batista, Teresa (2017)
The montado is a highly valuated biocultural landscape, typical of the Iberian Peninsula Southwest, traditionally related with agro-forestry-pastoral systems where open formations of scattered cork, holm or mix oaks compose the arboreous layer under which a rotation of crops/fallows/pastures is practised. This aesthetically pleasing and biologically rich landscape, nowadays protected by Portuguese and European Law, is a type of continuing landscape, according to the World Heritage Convention classification. It provides not only important environmental functions and services but also cultural ones, in particular the heritage which includes natural structures as well as tangible and intangible cultural elements. The montado intangible heritage values should be emphasized: cork and wood craftworks; gastronomy; local traditions and knowledge as oaks pruning, cork harvesting and folk medicine; beliefs and legends related with religious events, agro-pastoral works or megalithic monuments; traditional artistic activities. Developing the intangible heritage can enhance the montado socioeconomic sustainability through tourism, education and place attachment whose growth counteracts depopulation. Moreover, this development contributes to the montado attractiveness, through local activities (artistic and museologic inc.) and to material and spiritual wellbeing for visitors and local people, which leads also to a better sustainability of the montado. An example of project which takes into consideration the intangible heritage is the Montado Great Route (Grande Rota do Montado), launched by the Intermunicipal Community of Central Alentejo – CIMAC whose aim is the implementation of ca. 1.000 km of walking routes across the montado landscapes.